STRENGTHENING EARLY DETECTION OF RISK FACTORS AND CAPACITY BUILDING FOR ADOLESCENT GIRLS' HEALTH - yuniarti, yuniarti; rusmilawaty, rusmilawaty; Tunggal, Tri (Jurnal Rakat Sehat : Pengabdian Kepada Masyarakat, 2026)
Overcoming the problem of stunting must begin long before a child is born (the First 100 Days of Life period) and even since adolescent mothers to be able to break the chain of stunting in the life cycle. Adolescent girls have a greater risk of suffering from anemia because they often maintain body appearance by reducing food consumption and eating an unhealthy diet. An unhealthy and unbalanced diet will cause the body to experience nutrient deficiencies. Given these health problems, it is necessary to conduct stunting education since adolescence. Because in the future they will become prospective parents who will give birth to a stunting-free generation. The community service team provides solutions in terms of strengthening early detection of risk factors for stunting and improving the quality of adolescent girls' health through a series of steps, such as strengthening early detection of risk factors with adolescent health checks (height measurement, weight measurement, mid-upper arm circumference, color blindness test and hemoglobin check). Improving the health capacity of adolescent girls through increasing adolescents' understanding and knowledge about stunting and the dangers of stunting, knowledge about adolescent nutrition and consumption of blood supplement tablets. As well as promoting “Stunting Free Generation” and signing a joint commitment movement to prevent stunting. The output of this community service activity will produce community service publications in National Journals, articles in print media and videos of community service activities. The target achievement of this community service is to increase the understanding and knowledge of adolescent girls about reproductive health and the health of adolescent girls increases with an indicator of an increase in the Hemoglobin value of adolescent girls. This community service program is effective in increasing students' knowledge and awareness of their health. Risk factor screening carried out on 83 10th grade students of SMAN 3 Banjarbaru found 26 adolescents who have risk factors. The knowledge of adolescent girls about adolescent health is in the moderate category, there are still adolescent girls who do not understand about adolescent health, bmespecially about the risk factors for stunting that can occur in adolescence is anemia in adolescents. Adolescent girls were obedient to take Blood Addition tablets and formed a joint commitment to “Stunting Free Generation”.